Building community resilience in Easter Luzon: Women lead the way - Almeida, Olivia Ebenstål (CGIAR System Organization, 2024)
As communities navigate the twin challenges of climate change and social inequities, inspiring examples of adaptation, innovation, and women’s leadership are emerging. This article explores field insights from the Philippines, gathered as part of the CGIAR Research Initiative on Climate Resilience (ClimBeR) in collaboration with the International Institute of Rural Reconstruction (IIRR).